Impact of Roughness Length on WRF Simulated Land‐Atmosphere Interactions Over a Hyper‐Arid Region. Issue 6 (7th June 2020) - Nelli, Narendra Reddy; Temimi, Marouane; Fonseca, Ricardo Morais; Weston, Michael John; Thota, Mohana Satyanarayana; Valappil, Vineeth Krishnan; Branch, Oliver; Wulfmeyer, Volker; Wehbe, Youssef; Al Hosary, Taha; Shalaby, Abdeltawab; Al Shamsi, Noor; et al.
Abstract: The aerodynamic roughness length is a crucial parameter that controls surface variables including the horizontal wind, surface temperature, and heat fluxes. Despite its importance, in the Weather Research and Forecasting (WRF) model, this parameter is typically assigned a predefined value, mostly based on the dominant land‐use type. In this work, the roughness length is first estimated from eddy‐covariance measurements at Al Ain in the United Arab Emirates (UAE), a hyper‐arid region, and then ingested into WRF. The estimated roughness length is in the range 1.3–2.2 mm, one order smaller than the default value used in WRF. In line with previous studies, and from WRF model simulations during the warm and cold seasons, it is concluded that, when the roughness length is decreased by an order of magnitude, the horizontal wind speed increases by up to 1 m s −1, the surface temperature rises by up to 2.5°C, and the sensible heat flux decreases by as much as 10 W m −2 . In comparison with in situ station and eddy covariance data, and when forced with the updated roughness length, WRF gives more accurate 2‐m air temperature and sensible heat flux predictions. For prevailing wind speeds >6 m s −1, the model underestimates the strength of the near‐surface wind, a tendency that can be partially corrected, typically by 1–3 m s −1, when the updated roughness length is considered. For low wind speeds (<4 m s −1 ), however, WRF generally overestimates the strength of the wind. Key Points: For the first time, aerodynamic roughness length is estimated from in the United Arab Emirates, and it is one order smaller than the default value used in WRF WRF model 2‐m air temperature and sensible heat simulations are more accurate with the updated roughness length For wind speeds >6 m s −1, the model underestimates the strength of the surface wind, and it is corrected by 1–3 m s −1, when the updated roughness length is considered